Dubbing Multilingual Films: A New Challenge? - Heiss, Christine (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractOver the last ten years the number of films produced in the German speaking countries in which the communication takes place in more than one language has increased substantially. In addition to the necessity to render the information on the characters and plot transmitted by ‘intralinguistic’ variations which should never be flattened out in the dubbed version, interlinguistic differentiation must be taken into account in these films as well. A multiplicity of languages and different linguistic variations might therefore require a multiplicity of modes in film translation. Technical innovations like DVD might now open new possibilities to offer products of film translation which are better suited to deal with the new challenges presented by plurilinguistic films and to meet the linguistic sensibilities of different audience groups in the target culture.